2023
DOI: 10.3389/fnagi.2023.1153770
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel scoring system based on thrombosis and inflammation for predicting stroke-associated pneumonia: A retrospective cohort study

Abstract: BackgroundInflammation and thrombosis are involved in the development of stroke-associated pneumonia (SAP). Our aim was to evaluate the predictive value of a novel, simplified, thrombo-inflammatory prognostic score (TIPS) that combines both inflammatory and thrombus biomarkers in the early phase of ischemic stroke (IS).MethodsThe study population consisted of 897 patients with a first diagnosis of IS admitted to the emergency department of five tertiary hospitals in China. Of these, the data from 70% of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Notably, the implementation of TIPS based on D-dimer and PCT levels has improved the risk stratification of patients with sepsis ( Li et al, 2018 ). Moreover, TIPS has proven to be a valuable tool for the early identification of high-risk patients for SAP after IS ( Li et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the implementation of TIPS based on D-dimer and PCT levels has improved the risk stratification of patients with sepsis ( Li et al, 2018 ). Moreover, TIPS has proven to be a valuable tool for the early identification of high-risk patients for SAP after IS ( Li et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the current biomarkers and assessment tools fall short of their required clinical value. Our preliminary study showed that the combined use of thrombo-inflammatory markers can provide more prognostic information than a single thrombus or validated marker does ( Li et al, 2023 ). The thrombo-inflammatory prognostic score (TIPS) stands out as an emerging risk assessment tool with unique advantages.…”
Section: Introductionmentioning
confidence: 99%